FAKTOR-FAKTOR YANG MEMPENGARUHI NIAT BELI INSTAGRAM SHOPPING DI INDONESIA - Myrazteeva Charity Jacquelanne Mondigir; Margaretha Pink Berlianto (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2023)
The purpose of this study was to determine the effect of trust, attitude, perceived ease of use, perceived usefulness, and alternative evaluation on purchase intention, the effect of trust on attitude, and the effect of perceived ease of use on perceived usefulness on Instagram Shopping. In this study using non-probability sampling techniques with purposive sampling. This study uses a questionnaire by distributing to 186 respondents and filtered 160 respondents who intend to shop through Instagram Shopping. The data obtained is processed using the Smart PLS 3.2.9 application. From this study, the results obtained are trust has a positive effect on purchase intention, trust has a positive effect on attitude, attitude has a positive effect on purchase intention, perceived ease of use has a positive effect on purchase intention, perceived ease of use has a positive effect on perceived usefulness. However, there is no influence between perceived usefulness on purchase intention and there is no influence between alternative evaluation on purchase intention. The limitations in this study are that it only focuses on the Instagram Shopping platform and respondents only come from Indonesia. In this study, it is hoped that Instagram Shopping can improve and maintain several things in Instagram Shopping.